Multilocular Disseminated Tarlov Cysts: Importance of Imaging - Padma, Subramanyam (Medknow Publications & Media Pvt Ltd, 2014)
With technological advancements and wider availability of multimodality imaging, incidental lesions are frequently identified in patients undergoing various imaging studies. We report here a case of multiloculated disseminated perineural or Tarlov cysts (TCs). The primary aim of our study was to (1) provide a comprehensive review of the clinical, imaging and histopathological features of TCs (2) to draw attention to the fact that multiple lumbo-sacral and dorsal TCs can produce nerve injuries and serious movement disturbances (3) to document the usefulness of the magnetic resonance imaging (MRI) and bone scan in noninvasive diagnosis and guiding management in such cases. These cysts are clearly identified by MR and computerized tomography imaging of the lumbosacral spine. However, there are no reports on the scintigraphic findings of TCs in literature. TCs are typically benign, asymptomatic lesions that can simply be monitored. Until date, no consensus exists about the best surgical strategy to be followed for their management.